Factors Associated with Safe Infant Sleep Practices in Saudi Arabia - Al-shehri H; Almozaai R; Kariri M; Alhazmi Y; AlDakhel S; Alhunaishel R; Aladhadhi D (Dove Medical Press, 2021)
Hassan Al-shehri,1 Rahaf Almozaai,2 Marwh Kariri,2 Yara Alhazmi,2 Shatha AlDakhel,2 Reyouf Alhunaishel,2 Dina Aladhadhi2 1Department of Pediatrics, College of Medicine, Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi Arabia; 2College of Medicine, Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi ArabiaCorrespondence: Hassan Al-shehriDepartment of Pediatrics, College of Medicine, Imam Mohammad Ibn Saud Islamic University, Riyadh, Saudi ArabiaTel +966112582759Email haalshehri@imamu.edu.saPurpose: To assess mothers' approaches to infant sleep practices.Patients and Methods: A cross-sectional survey study was conducted on mothers with babies aged below five months who were attending paediatric clinics between November 1st, 2020, and January 5th, 2021, in Riyadh, Saudi Arabia.Results: A total of 522 mothers participated in this study. A total of 38.9% practised exclusive formula feeding. A total of 61.9% of the participants practised the supine position. The majority (93.3%) of the mothers shared a room with their babies, while 34.7% shared a bed. Only 6.9% did not use any soft bedding. Age was a significant predictor associated with participant practices regarding sleeping and feeding positions (p < 0.05). Having two or more children was associated with improper sleeping practices (p < 0.05). Being non-Saudi and having a university degree or higher were associated with having a higher risk of unsafe practices regarding bed-sharing (p < 0.05). On the other hand, being contacted by a doctor, nurse, or other healthcare worker about safe sleep practices were an important factor that influenced safe practices regarding feeding (p < 0.05). Receiving care at a private hospital was associated with safer practices regarding sleeping position and bed-sharing (p < 0.05).Conclusion: We observed high-risk sleeping practices among Saudi mothers. This includes using soft bedding and unsafe sleeping positions. The importance of this study lies in the future implementation of this result through public health measures aimed at at-risk populations.Keywords: practices, Saudi Arabia, sleep, sudden infant death syndrome